Insertion of long interspersed element‐1 in the Mitf gene is associated with altered neurobehavior of the black‐eyed white Mitfmi‐bw mouse. (4th December 2013) - Takeda, Kazuhisa; Hozumi, Hiroki; Nakai, Kunihiko; Yoshizawa, Miki; Satoh, Hiroshi; Yamamoto, Hiroaki; Shibahara, Shigeki
<x xml:space="preserve">Abstract</x> Microphthalmia‐associated transcription factor (Mitf) is required for the differentiation of melanoblasts of the neural crest origin. The mouse homozygous for the black‐eyed white (Mitfmi‐bw) allele is characterized by white‐coat color and deafness with black eye, due to the loss of melanoblasts during embryonic development. The Mitfmi‐bw allele carries an insertion of long interspersed element‐1 (L1) in intron 3 of the Mitf gene, which may cause the deficiency of melanocyte‐specific Mitf‐M. Here, we show that the L1 insertion results in the generation of alternatively spliced Mitf‐M mRNA species, such as Mitf‐M mRNA lacking exon 3, exon 4 or both exons 3 and 4, each of which encodes Mitf‐M protein with an internal deletion. Transient expression assays showed the loss of or reduction in function of each aberrant Mitf‐M protein and the dominant negative effect of Mitf‐M lacking exon 4 that encodes an activation domain. Thus, the L1 insertion may decrease the expression level of functional Mitf‐M. Importantly, Mitf‐M mRNA is expressed in the wild‐type mouse brain, with the highest expression level in the hypothalamus. Likewise, aberrant Mitf‐M mRNAs are expressed in the bw mouse brain. The bw mice show the altered neurobehavior under a stressful environment, suggesting the role of Mitf‐M in sensory perception.